Modulo N Backoff Scheme for Effective QoS Differentiation and Increased Bandwidth Utilization in IEEE 802.11 Networks - Janczak, Tomasz; Konorski, Jerzy; Woźniak, Józef; Pawlikowski, Krzysztof (Journal of Telecommunications and Information Technology, 2009)
The paper presents a new modulo N channel access scheme for wireless local area networks (WLANs). The novel solution derives from the distributed coordination function (DCF) of the IEEE 802.11 standard, further elaborated as enhanced distribution channel access (EDCA) by the 802.11e draft specification. The main innovation concerns improvement of the binary exponential backoff scheme used for collision avoidance in 802.11 networks. The most appealing feature of the new modulo N backoff scheme is that it outperforms the original 802.11 solution in terms of channel utilization ratio under any traffic conditions. Furthermore, the modulo N proposal can be naturally augmented with QoS differentiation mechanisms like 802.11e extensions. The prioritized modulo N scheme achieves better throughput-delay characteristics for multimedia traffic when compared with the original 802.11e proposal. At the same time, the new solution retains backward compatibility and includes all features which have made IEEE 802.11 networks extremely popular nowadays.
Keywords: channel access; MAC; performance analysis; random backoff; WLAN